An orientable foamed high-ductility cement-based composite composition and its use

CN118063154BActive Publication Date: 2026-10-16FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211477906.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-23
Publication Date
2026-10-16
Estimated Expiration
2042-11-23

AI Technical Summary

Technical Problem

[0003]纤维在水泥基材料受力开裂阶段可有效发挥桥联作用限制裂纹扩展,但单一尺寸的纤维只能在裂纹扩展的某一阶段限制宏观裂缝或微裂纹,而水泥基材料具有多尺度破坏特征,同时单一尺寸的纤维会使复合材料需要加入较多量的纤维来改进某一性能,容易带来粘度大、成本高、孔隙率增高等不利于加工及改进其他性能的影响,因此丰富增强体尺度是制备性能更加优秀稳定的水泥基复合材料的一个主要研究方向

Benefits of technology

[0071](1) After the activated carbon on the surface of PVA fiber adsorbs isocyanate, it can synthesize polyurethane prepolymer on the surface of PVA fiber to obtain modified PVA fiber. Modified PVA fiber can become foaming core with prepolymer. After the modified PVA fiber is added to cement mortar, the polyurethane prepolymer on its surface can foam along the direction of the PVA fiber surface to achieve oriented foaming. Oriented foaming can effectively disperse PVA fiber and maintain dispersion stability. The expansion property of polyurethane foam structure can enhance the density of concrete between foams.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003960047640000111
    Figure BDA0003960047640000111
  • Figure BDA0003960047640000121
    Figure BDA0003960047640000121
  • Figure BDA0003960047640000131
    Figure BDA0003960047640000131
Patent Text Reader

Abstract

The application discloses a high-toughness cement-based composite material composition and a preparation method and application thereof. The cement-based composite material composition comprises at least cement, silica fume, nano microbeads, sand, a water reducing agent, modified PVA fibers and modified graphene. The modified PVA fibers and the modified graphene are used in the cement-based composite material composition, and the cement-based composite material composition is used for preparing concrete, so that the toughness and mechanical properties of the concrete can be further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fiber-reinforced cement-based composite materials, specifically relating to a high-toughness cement-based composite material composition and its application. Background Technology

[0002] Cement is a powdered, hydraulic inorganic gel material that forms a paste when mixed with water. It hardens in air or, more effectively, in water. As an important gel material, cement effectively binds sand and gravel together and is widely used in civil engineering, water conservancy, and other fields. With modernization, national requirements for materials are constantly increasing, and cement-based materials have become crucial for social construction. However, cement-based materials have significant drawbacks, including high brittleness. To overcome these shortcomings and improve toughness, fibers are used as reinforcements to prepare fiber-reinforced cement-based composites with better overall toughness. Fiber-reinforced cement-based composites can effectively improve the high brittleness of cement-based materials, but they exhibit significant strain softening and single-crack or few-crack cracking modes. Strain hardening and multi-crack cracking are the goals pursued by high-toughness cement-based composites.

[0003] Fibers can effectively bridge cracks and limit their propagation during the stress-cracking stage of cement-based materials. However, single-sized fibers can only limit macroscopic or microcracks at a certain stage of crack propagation. Cement-based materials exhibit multi-scale failure characteristics, and single-sized fibers require a large amount of fiber to improve a specific property, which can lead to high viscosity, high cost, and increased porosity, hindering processing and improving other properties. Therefore, enriching the reinforcing structure is a major research direction for preparing cement-based composite materials with superior and stable performance. CN111777387A discloses a high-strength concrete with added PVA fibers and graphene and its preparation method. The concrete reinforcement consists of large-scale PVA fibers and small-scale graphene, which can work synergistically to enhance the mechanical properties of concrete at multiple scales. However, this disclosed method does not address the improvement and stabilization of fiber dispersion, and it mainly improves the strength of the concrete, with little mention of improving or applying its toughness.

[0004] To overcome the low toughness of cement-based materials, expand their application range, and enhance their overall performance, while enriching the fiber reinforcement system added to cement-based materials, it is necessary to consider improving the dispersion stability of fibers to further improve the toughness of cement-based materials. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention proposes a high-toughness cement-based composite material, which possesses good toughness and strength.

[0006] The technical solution of the present invention is as follows:

[0007] A cement-based composite material composition comprising at least: cement, silica fume, nanospheres, sand, water-reducing agent, modified PVA fiber, and modified graphene.

[0008] According to an embodiment of the present invention, the raw materials comprise, per 100 parts by weight of cement:

[0009] 100 parts by weight of cement, 3-6 parts by weight of silica fume, 10-17 parts by weight of nanospheres, 100-120 parts by weight of sand, 1.2 parts by weight of water-reducing agent, 1-5 parts by weight of modified PVA fiber, and 0.05-0.1 parts by weight of modified graphene.

[0010] According to an embodiment of the present invention, the cement is selected from silicate cement. Preferably, the strength grade of the cement is not less than PO 52.5.

[0011] According to an embodiment of the present invention, the SiO2 content in the silica fume is greater than 89%.

[0012] According to an embodiment of the present invention, the performance parameters of the nanospheres are as follows: average particle size ≤ 1.0 μm, apparent density 0.8~1 g / cm³. 3 Its density is 2.52 g / cm³. 3 The compressive strength of the sphere is ≥800MPa.

[0013] According to an embodiment of the present invention, the sand is selected from natural river sand. Preferably, the performance parameters of the natural river sand are as follows: fineness modulus of 2 to 3, preferably 2.5; mud content ≤1%.

[0014] According to an embodiment of the present invention, the water-reducing agent is a polycarboxylate superplasticizer. The polycarboxylate superplasticizer can be any polycarboxylate superplasticizer known in the art, and is not specifically limited in this invention. For example, the polycarboxylate superplasticizer may be a composite polycarboxylate superplasticizer (e.g., purchased from Hongxiang Building Admixture Factory in Laiyang City, Shandong Province).

[0015] According to an embodiment of the present invention, the modified graphene is preferably 0.06 to 0.08 parts by weight per 100 parts by weight of cement.

[0016] According to an embodiment of the present invention, the modified PVA fiber is preferably 2 to 3 parts by weight per 100 parts by weight of cement.

[0017] According to an embodiment of the present invention, the modified graphene is selected from polydopamine-modified graphene. Preferably, the polydopamine-modified graphene is prepared by reacting graphene with a dopamine solution.

[0018] More preferably, the preparation method of the polydopamine-modified graphene includes the following steps:

[0019] A1) Preparation of dopamine solution: Obtain dopamine solution by mixing acidic buffer solution and dopamine source;

[0020] A2) Graphene and dopamine solution mixed reaction: Add graphene to the dopamine solution, and after the graphene is completely immersed in the dopamine solution, the reaction begins;

[0021] After the reaction (A3) is complete, the precipitate is collected to obtain polydopamine-modified graphene.

[0022] Specifically, in step A1), the mass concentration of dopamine in the dopamine solution is 0.1 to 5 g / L, for example, 2 g / L.

[0023] Specifically, in step A1), an alkaline regulator is added to adjust the pH of the dopamine solution to be greater than 7, preferably greater than 8, for example, 8.5. Further, the alkaline regulator is selected from substances known in the art, such as sodium hydroxide solution.

[0024] Specifically, in step A1), the acidic buffer is selected from acidic buffers known in the art, such as hydrochloric acid buffer, like tris-HCl buffer (Tris-HCl buffer).

[0025] Specifically, in step A1), the dopamine source is selected from dopamine hydrochloride.

[0026] Specifically, in step A2), the mass ratio of dopamine to graphene in the dopamine source is 1 to 3:1, preferably 2:1.

[0027] Specifically, in step A2), the reaction is carried out in an air atmosphere. Further, the reaction conditions are: stirring at 10–40°C for 1–30 hours, preferably at 20–30°C for 24 hours.

[0028] Specifically, in step A3), the collection of precipitate can be carried out using methods known in the art, as long as precipitate can be obtained, such as centrifugation and / or washing.

[0029] According to an embodiment of the present invention, the modified PVA fiber is obtained by introducing a polyurethane prepolymer into the PVA fiber. Preferably, the polyurethane prepolymer can be foamed along the surface direction of the PVA fiber to achieve oriented foaming. The oriented foamed modified PVA fiber can effectively disperse the PVA fiber and keep it in stable dispersion, while the expansibility of the foam structure on the surface of the PVA fiber can enhance the density of the concrete.

[0030] Preferably, the length of the modified PVA fiber is selected from 1 to 15 mm, for example, 3 mm and / or 12 mm. Exemplarily, the mass ratio of modified PVA fiber with a length of 6 mm to modified PVA fiber with a length of 12 mm is 1.5:1.

[0031] Preferably, the PVA fiber is selected from high-modulus PVA fiber. Further, the tensile strength of the PVA fiber is 1200–1400 MPa, for example, 1300 MPa.

[0032] Preferably, the length of the PVA fiber is selected from 1 to 15 mm, for example, 3 mm or 12 mm; the diameter of the PVA fiber is 0.1 to 0.2 nm, for example, 0.18 nm; and the density of the PVA fiber is 0.9 to 1 g / cm³. 3 For example, 0.91 g / cm³ 3 .

[0033] For example, the PVA fiber is purchased from Shandong Taicheng Fiber Co., Ltd., and the length of the PVA fiber is selected from 1 to 15 mm, for example, 3 mm or 12 mm.

[0034] Preferably, the polyurethane prepolymer is obtained by reacting a polymer with an isocyanate.

[0035] Further, the polymer is selected from polypropylene glycol (PPG), and the molecular weight of the polypropylene glycol is preferably 300-800, for example, 600. For example, the polypropylene glycol (PPG) has a molecular weight of 600 (purchased from Shandong Jiaying Technology Co., Ltd.).

[0036] Preferably, the isocyanate is a diisocyanate monomer, which may be toluene diisocyanate (TDI) or diphenylmethane diisocyanate (MDI). For example, the diisocyanate is MDI (e.g., purchased from Huntsman Polyurethanes Co., Ltd., Shanghai).

[0037] According to an embodiment of the present invention, the method for preparing the modified PVA fiber includes the following steps:

[0038] B1) After adsorbing activated carbon onto the surface of the PVA fiber, PVA fiber with activated carbon embedded in its surface is obtained;

[0039] B2) The PVA fibers with activated carbon embedded on the surface obtained in step B1) are immersed in a mixture containing isocyanate and subjected to vacuum treatment.

[0040] B3) After vacuum treatment, the fiber with activated carbon embedded on its surface, which was immersed in the mixture containing isocyanate in B2), is heated and stirred under an inert atmosphere. First, the polymer is added dropwise to the reaction system, and then the isocyanate is added dropwise. After the addition is completed, the temperature is raised and the reaction is carried out to obtain a polyurethane prepolymer on the surface of the PVA fiber, which is the modified PVA fiber.

[0041] According to an embodiment of the present invention, in step B1), the mass ratio of activated carbon to PVA fiber is (0.1-5):1, for example, 2:1 or 1:1.

[0042] According to an embodiment of the present invention, in step B1), the adsorption specifically includes: uniformly spreading the activated carbon on the PVA fibers, and obtaining PVA fibers with activated carbon embedded in their surface by hot pressing. Preferably, the hot pressing conditions include: a hot pressing time of 1 to 10 minutes, for example, 5 minutes; a hot pressing pressure of 1000 to 1100 psi, for example, 1015 psi; and a hot pressing temperature of 50 to 100°C, for example, 90°C.

[0043] According to an embodiment of the present invention, in step B1), preferably, the activated carbon is selected from powdered activated carbon, and its mesh size is selected from 200 to 300, for example 250.

[0044] According to an embodiment of the present invention, in step B2), the mixture containing isocyanate comprises isocyanate and an organic solvent. Preferably, the mass ratio of isocyanate to organic solvent is (0.1-1):(0.1-1), for example, 1:1. Preferably, the organic solvent is selected from acetone or toluene.

[0045] According to an embodiment of the present invention, in step B2), the vacuum treatment conditions include: a vacuum treatment time of 1 to 10 minutes, for example, 5 minutes; a vacuum degree of -0.08 to -0.1 MPa, for example, -0.09 MPa; and a vacuum treatment temperature of 20 to 40°C, for example, 30°C. For example, the vacuum treatment conditions may be: vacuum treatment for 6 minutes at 35°C and a vacuum degree of -0.09 MPa.

[0046] According to an embodiment of the present invention, in step B3), the inert atmosphere may be a gas known in the art, such as N2.

[0047] According to an embodiment of the present invention, in step B3), the heating temperature is not less than 50°C, for example, 60°C.

[0048] According to an embodiment of the present invention, in step B3), the mass ratio of the polymer to the isocyanate is (0.1-2):2, for example, 1:2.

[0049] According to an embodiment of the present invention, in step B3), when the temperature is increased, the rate of temperature increase is 20 to 40 °C / h, for example, 35 °C / h.

[0050] The present invention also provides the application of the above-described cement-based composite material composition, for example, in the preparation of concrete.

[0051] The present invention also provides a concrete comprising at least the above-described cement-based composite material composition.

[0052] According to an embodiment of the present invention, the cement-based composite material composition may further include or exclude water.

[0053] Preferably, the mass ratio of cement to water in the cement-based composite material composition is 1:(0.1-1), more preferably 1:0.36-0.38.

[0054] The present invention also provides a method for preparing the above-mentioned concrete, which includes the following steps:

[0055] 1) The modified graphene is added to the first part of water and mixed to obtain an aqueous solution of modified graphene.

[0056] 2) After mixing the silica fume, nanospheres and cement until uniform, quickly stir to obtain the first mixture;

[0057] 3) Dissolve the water-reducing agent in the second part of the water and stir it evenly. Then add it to the first mixture in step 2) in two batches, stirring quickly after each addition to obtain the second mixture.

[0058] 4) After mixing, keep stirring the second mixture obtained in step 3) at a low speed, slowly add the aqueous solution of the modified graphene while stirring, and then stir quickly to obtain the cement mixture.

[0059] 5) After the catalyst and polyol are mixed evenly, the modified PVA fiber is added and stirred quickly to obtain a mixture. Then, the mixture is quickly poured into the cement mixture in step 4) and stirred slowly to obtain a cement-based composite material.

[0060] According to an embodiment of the present invention, the total amount of the first part of water and the second part of water is in a mass ratio of 1:(0.1 to 1) to cement, preferably 1:0.36 to 0.38.

[0061] According to an embodiment of the present invention, the mass ratio of the first portion of water to the second portion of water is not specifically required, as long as the above-mentioned aqueous solution can be obtained. For example, the mass ratio of the first portion of water to the second portion of water is 1:0.6.

[0062] According to an embodiment of the present invention, in the concrete preparation method, slow mixing refers to a mixing speed of 50-60 r / min, and fast mixing refers to a mixing speed of 140-150 r / min.

[0063] According to an embodiment of the present invention, in the concrete preparation method, the rapid mixing time in steps 2) and 3) is no more than 60s, for example, 60s, 5s, or 10s.

[0064] According to an embodiment of the present invention, in the concrete preparation method, in step 4), the slow stirring time is no more than 10 minutes, for example, 5 minutes or 30 seconds.

[0065] According to an embodiment of the present invention, in step 5), the catalyst is a mixed catalyst of a tertiary amine compound and an organotin compound. Further, the tertiary amine compound may be triethylenediamine or triethylamine. Further, the organotin compound may be dibutyltin dilaurate. Further, the mass ratio of the tertiary amine compound to the organotin compound is 1:0.5 to 0.8. Exemplarily, the catalyst is triethylamine and dibutyltin dilaurate, with a mass ratio of 1:0.5.

[0066] According to an embodiment of the present invention, in step 5), the polyol is selected from pentaerythritol and / or glycerol.

[0067] According to an embodiment of the present invention, in step 5), the mass ratio of the catalyst, polyol and modified PVA fiber is 1:(10-20):(10-30), for example, 1:15:20.

[0068] According to an embodiment of the present invention, in step 5), after the modified PVA fiber is added to the cement mixture, the polyurethane prepolymer on the surface of the modified PVA fiber foams along the surface direction of the PVA fiber to achieve oriented foaming. The oriented foamed modified PVA fiber can effectively disperse the PVA fiber and keep it dispersed stably, while the expansion property of the polyurethane foam structure on the surface of the PVA fiber can enhance the density of the concrete between fiber units.

[0069] The present invention also provides the application of the above-mentioned concrete in the field of construction, such as for the connection, reinforcement or repair of bridge decks, and the preparation of earthquake-resistant energy-dissipating materials.

[0070] The beneficial effects of this invention are as follows:

[0071] (1) After the activated carbon on the surface of PVA fiber adsorbs isocyanate, it can synthesize polyurethane prepolymer on the surface of PVA fiber to obtain modified PVA fiber. Modified PVA fiber can become foaming core with prepolymer. After the modified PVA fiber is added to cement mortar, the polyurethane prepolymer on its surface can foam along the direction of the PVA fiber surface to achieve oriented foaming. Oriented foaming can effectively disperse PVA fiber and maintain dispersion stability. The expansion property of polyurethane foam structure can enhance the density of concrete between foams.

[0072] (2) Polydopamine-modified graphene is obtained by modifying graphene with polydopamine PDA. This can enhance the dispersibility of graphene in concrete, improve the interfacial bonding of graphene in concrete, thereby better play the filling role, reduce the porosity in concrete, make concrete more compact, and improve mechanical properties. At the same time, graphene with high strength and high modulus of two-dimensional structure can also play a certain role in limiting the propagation of microcracks.

[0073] (3) Using a PVA fiber network as a framework, an oriented polyurethane foam structure is introduced to form a unit with fibers as the core and foam structure as the wrapping layer, further enriching the three-dimensional toughening system in concrete. The high modulus of the fibers and the elasticity of the foam improve the toughness of the cement-based composite material. This invention also disperses modified graphene with a two-dimensional structure in cement, which can enhance the toughness of concrete at multiple scales while ensuring the stability of other mechanical properties. Detailed Implementation

[0074] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.

[0075] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available products or can be prepared by known methods.

[0076] Preparation Example 1

[0077] The preparation method of polydopamine-modified graphene is as follows:

[0078] A1) Tris(hydroxymethyl)aminomethane hydrochloride (Tris-HCl) and dopamine hydrochloride were dissolved in deionized water. The pH of the solution was adjusted to 8.5 with sodium hydroxide under magnetic stirring to obtain a 2 g / L dopamine solution.

[0079] A2) Based on the mass ratio of dopamine:graphene = 2:1, take an appropriate amount of graphene and add it to the polyamine solution. Sonicate until the graphene is completely immersed in the solution, and stir the reaction at room temperature in an air atmosphere for 24 hours.

[0080] A3) After the reaction is complete, the solution is centrifuged to remove the supernatant. The precipitate is then added to deionized water and subjected to sonication and centrifugation until the supernatant is colorless. Finally, the precipitate is collected by centrifugation to obtain polydopamine-modified graphene.

[0081] Preparation Example 2

[0082] The preparation method of modified PVA fibers is as follows:

[0083] B1) Take PVA fiber and powdered activated carbon, with a mass ratio of activated carbon to PVA fiber of 1:1. Divide the powdered activated carbon into two equal parts and spread them evenly in a mold with alternating layers of powdered activated carbon and fiber (i.e., powdered activated carbon is alternately spread on the top and bottom of PVA fiber) for hot pressing. The hot pressing time is 5 minutes, the hot press pressure is 1015 psi, and the hot pressing temperature is 90℃. After the hot pressing is completed, remove the fiber and cool it to room temperature to obtain PVA fiber with activated carbon embedded on the surface.

[0084] B2) The PVA fibers with activated carbon embedded in the surface obtained in step 1) are immersed in a mixture of isocyanate and acetone, wherein the mass ratio of isocyanate to acetone is 1:1. The PVA fibers immersed in the mixture are placed in a vacuum chamber and vacuumed.

[0085] B3) After vacuum treatment, the PVA fibers impregnated with the mixture were transferred to a N2 atmosphere for heating and stirring. PPG (molecular weight 600, purchased from Shandong Jiaying Technology Co., Ltd.) was gradually added dropwise to the solution, followed by isocyanate. After the addition was complete, the temperature was raised and the reaction was carried out for 1 hour. The mass ratio of PPG to isocyanate was 1:2. The stirring start temperature was 60℃ and the temperature change rate was 35℃ / h.

[0086] After the reaction of B4 is completed, modified PVA fibers are obtained.

[0087] In step B1), the PVA fiber used was purchased from Shandong Taicheng Fiber Co., Ltd., with a diameter of 0.18 mm, a tensile strength of 1540 MPa, and a density of 0.91 g / cm³. 3 Modified PVA fibers with a length of 3 mm and 12 mm were prepared using the above method and then used for later use.

[0088] Example 1

[0089] 1. The raw materials for preparing cement-based composite materials include at least cement, silica fume, nanospheres, natural river sand, water-reducing agent, modified PVA fiber, and modified graphene.

[0090] The mass ratio of cement, silica fume, nanospheres, sand, water, water-reducing agent, modified PVA fiber, and modified graphene is: 1:0.03:0.17:1.2:0.38:0.012:0.02:0.0006;

[0092] The specific parameters of the above raw materials are as follows:

[0093] 1) Cement: Silicate cement, strength grade PO 52.5;

[0094] 2) Natural river sand: fineness modulus 2.5, apparent density 2660 kg / m³ 3 Bulk density 1573 kg / m³ 3 The mud content should be ≤1%.

[0095] 3) The silica fume should contain more than 89% SiO2;

[0096] 4) Nanospheres: Average particle size ≤ 1.0 μm, apparent density 0.9 ± 0.1 g / cm³ 3 Its density is 2.52 g / cm³. 3 The compressive strength of the sphere must be ≥800MPa;

[0097] 5) Water-reducing agent: Composite polycarboxylate high-efficiency water-reducing agent, purchased from Hongxiang Building Admixture Factory in Laiyang City, Shandong Province;

[0098] 6) Composite catalyst: It is obtained by mixing triethylamine and dibutyltin dilaurate. The purity of triethylamine is 99.5% and the purity of dibutyltin dilaurate is 98%. The ratio of triethylamine to dibutyltin dilaurate is 1:0.5.

[0099] 7) PPG-400: 99% purity, purchased from Shandong Yousuo Chemical Technology Co., Ltd.

[0100] 8) Modified graphene: The modified graphene of Example 1 was prepared;

[0101] 9) Modified PVA fiber: The modified PVA fiber of Example 2 was prepared with a mass ratio of 1.5:1 for modified PVA fiber with a length of 6 mm and modified PVA fiber with a length of 12 mm.

[0102] 2. Preparation of high-toughness concrete, the preparation method includes the following steps:

[0103] 1) Take a portion of deionized water and mix it with modified graphene, and disperse it evenly by ultrasonication to obtain an aqueous solution of modified graphene.

[0104] 2) Add silica fume, nanospheres, and cement to a mechanical mixer and mix until homogeneous. Add fiber and sand, and mix quickly for 60 seconds to obtain the first mixture.

[0105] 3) Dissolve the composite polycarboxylate superplasticizer (purchased from Hongxiang Building Admixture Factory in Laiyang City, Shandong Province) in an appropriate amount of deionized water. Add it to the first mixture in two portions, stirring quickly for 60 seconds after each addition to obtain the second mixture.

[0106] 4) After mixing, the second mixture is stirred at low speed in a mechanical mixer, an aqueous solution of modified graphene is added, and finally it is stirred rapidly for 5 minutes to obtain the cement mixture.

[0107] 5) Take the catalyst (triethylamine and dibutyltin dilaurate, with a mass ratio of 1:0.5) and pentaerythritol, mix them evenly, then add the modified PVA fiber and stir quickly for 5-10 seconds to obtain a mixture. Then quickly pour the modified PVA fiber and the mixture into the cement mixture in step 4) and stir slowly for 30 seconds to obtain a uniform cement mortar; wherein, the mass ratio of the catalyst, pentaerythritol and modified PVA fiber is 1:15:20.

[0108] After the modified PVA fiber is added to the cement mixture, the polyurethane prepolymer on the surface of the modified PVA fiber foams along the surface direction of the PVA fiber to achieve oriented foaming, thereby obtaining high-modulus PVA fiber wrapped in an oriented polyurethane foam structure.

[0109] 6) Pour the well-mixed concrete mixture into the test mold in two batches, and compact the concrete after each pour. The test mold size is 40mm×40mm×160mm.

[0110] 7) After 12 hours, remove the sample from the mold and cure it for the required age for testing. The relative humidity for curing is 90% and the temperature is 20±2℃.

[0111] The mechanical strength of the test specimens was tested according to GB 17671-1999, and the results are shown in Table 1.

[0112] Table 1. Test results of the sample in Example 1

[0113]

[0114] Note: "28d" in the table refers to the test results taken after 28 days of standard maintenance, and the same applies below.

[0115] Examples 2-4

[0116] 1. Prepare the raw materials for the high-toughness cement-based composite material. The process is basically the same as step 1 in Example 1, except that the quality of the raw materials is as follows:

[0117] The mass ratio of cement, silica fume, nanospheres, sand, water, water-reducing agent, modified PVA fiber, and modified graphene in Example 2 is as follows: 1:0.04:0.12:1:0.012:0.37:0.03:0.0008;

[0119] The mass ratio of cement, silica fume, nanospheres, sand, water, water-reducing agent, modified PVA fiber, and modified graphene in Example 3 is as follows: 1:0.06:0.10:1.1:0.012:0.36:0.028:0.0007;

[0121] The mass ratio of cement, silica fume, nanospheres, sand, water, water-reducing agent, modified PVA fiber, and modified graphene in Example 4 is as follows:

[0122] 1:0.05:0.15:1:0.37:0.012:0.025:0.0006.

[0123] 2. Preparation of high-toughness concrete is basically the same as step 2 in Example 1, except that the raw materials of the corresponding cement-based composite material are selected.

[0124] The mechanical strength of the test specimens was tested according to GB 17671-1999. The test results of Examples 2-4 are shown in Table 2.

[0125] Table 2 Test results of samples from Examples 2-4

[0126]

[0127] Comparative Example 1

[0128] 1. Prepare the raw materials for the high-toughness cement-based composite material, which are basically the same as in Example 4, except that unmodified graphene is added to the raw materials of the cement-based composite material.

[0129] 2. Preparation of high-toughness concrete is basically the same as step 2 in Example 4, except that the raw materials of the above-mentioned cement-based composite material in this comparative example are selected.

[0130] Comparative Example 2

[0131] 1. Prepare the raw materials for the high-toughness cement-based composite material. The raw materials are basically the same as those in Example 4. The difference is that PVA fibers, i.e., unmodified high-modulus PVA fibers, are added to the raw materials of the cement-based composite material.

[0132] 2. Preparation of high-toughness concrete is basically the same as step 2 in Example 4, except that the raw materials of the above-mentioned cement-based composite material in this comparative example are selected.

[0133] The mechanical strength of the test specimens was tested according to GB 17671—1999. The test results of Comparative Examples 1-3 are shown in Table 3.

[0134] Table 3 shows the test results of the comparative samples.

[0135]

[0136] The test results above show that:

[0137] Comparing the test results of Example 4 and Comparative Example 1, it was found that the flexural strength of the cement-based composite material with added unmodified graphene decreased by 2.9%, and the compressive strength decreased by 8.5%. The inventors believe that this may be because graphene has a large surface energy and is prone to agglomeration, which increases the porosity of the concrete after its addition. In addition, the interface between graphene and concrete is not tight enough, so it cannot play a good role in filling and limiting crack propagation.

[0138] Comparing the test results of Example 4 and Comparative Example 2, it was found that the compressive strength of the cement-based composite material using unmodified high-modulus PVA fibers decreased by 4.4%, while the flexural strength decreased by 20.8%. The inventors believe this may be because Example 4 used an oriented polyurethane foam structure to encapsulate the high-modulus PVA fibers, enriching the toughening network system and improving the toughness of the concrete. The polyurethane foam can make the PVA fibers disperse evenly and stably, reducing porosity, and the expansion property of the polyurethane foam can increase the density, thus improving the compressive strength of the concrete.

[0139] The exemplary embodiments of the present invention have been described above. However, the scope of protection of this application is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made by those skilled in the art within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A cement-based composite material composition, characterized in that, Based on 100 parts by weight of cement, the cement-based composite material composition comprises at least: 100 parts by weight of cement, 3-6 parts by weight of silica fume, 10-17 parts by weight of nanospheres, 100-120 parts by weight of sand, 1.2 parts by weight of water-reducing agent, 1-5 parts by weight of modified PVA fiber, and 0.05-0.1 parts by weight of modified graphene. The performance parameters of the nanospheres are as follows: average particle size ≤ 1.0 μm, apparent density 0.8~1 g / cm³. 3 Its density is 2.52 g / cm³. 3 The compressive strength of the sphere is ≥800MPa; The modified graphene is selected from polydopamine-modified graphene, which is prepared by reacting graphene with a dopamine solution. The method for preparing the modified PVA fiber includes the following steps: B1) After adsorbing activated carbon onto the surface of the PVA fiber, PVA fiber with activated carbon embedded in its surface is obtained; the activated carbon is evenly spread on the PVA fiber and hot-pressed to obtain PVA fiber with activated carbon embedded in its surface. B2) The PVA fibers with activated carbon embedded on the surface obtained in step B1) are immersed in a mixture containing isocyanate and subjected to vacuum treatment; B3) After vacuum treatment, the PVA fibers with activated carbon embedded on the surface of the mixture containing isocyanate in B2) are heated and stirred in an inert atmosphere. First, the polymer is added dropwise to the reaction system, and then the isocyanate is added dropwise. After the addition is completed, the temperature is raised and the reaction is carried out to obtain a polyurethane prepolymer on the surface of the PVA fibers, which is the modified PVA fiber.

2. The cement-based composite material composition according to claim 1, characterized in that, The cement is selected from silicate cement; the strength grade of the cement is not less than PO 52.

5.

3. The cement-based composite material composition according to claim 1, characterized in that, The silica ash contains more than 89% SiO2. The sand is selected from natural river sand; The water-reducing agent is a polycarboxylate superplasticizer.

4. The cement-based composite material composition according to claim 1, characterized in that, The modified graphene is 0.06 to 0.08 parts by weight per 100 parts by weight of cement; The preparation method of the polydopamine-modified graphene includes the following steps: A1) Preparation of dopamine solution: Obtain dopamine solution by mixing acidic buffer solution and dopamine source; A2) Graphene and dopamine solution mixed reaction: Add graphene to the dopamine solution, and after the graphene is completely immersed in the dopamine solution, the reaction begins; After the reaction is complete (A3), the precipitate is collected to obtain polydopamine-modified graphene.

5. The cement-based composite material composition according to claim 1, characterized in that, The modified PVA fiber is 2-3 parts by weight per 100 parts by weight of cement; In step B1), the hot pressing conditions include: hot pressing time of 1 to 10 minutes; hot pressing pressure of 1000 to 1100 psi; and hot pressing temperature of 50 to 100°C. In step B2), the vacuum treatment conditions include: vacuum treatment time of 1 to 10 minutes; vacuum degree of -0.08 to -0.1 MPa; and vacuum treatment temperature of 20 to 40°C. In step B3), the heating temperature is not less than 50°C; In step B3), the mass ratio of the polymer to the isocyanate is 0.1~2:2; In step B3), when the temperature is increased, the rate of increase is 20~40℃ / h.

6. The use of the cement-based composite material composition according to any one of claims 1-5.

7. A type of concrete comprising at least the cement-based composite material composition according to any one of claims 1-5.

8. The concrete according to claim 7, characterized in that, The cement-based composite material composition may or may not include water; The mass ratio of cement to water in the cement-based composite material composition is 1:0.1~1.

9. The method for preparing concrete according to claim 7 or 8, characterized in that, It includes the following steps: 1) The modified graphene is added to the first part of water and mixed to obtain an aqueous solution of modified graphene. 2) After mixing the silica fume, nanospheres and cement until uniform, quickly stir to obtain the first mixture; 3) Dissolve the water-reducing agent in the second part of the water and stir it evenly. Then add it to the first mixture in step 2) in two batches, stirring quickly after each addition to obtain the second mixture. 4) After mixing, keep stirring the second mixture obtained in step 3) at a low speed, slowly add the aqueous solution of the modified graphene while stirring, and then stir quickly to obtain the cement mixture. 5) After uniformly mixing the catalyst and polyol, add the modified PVA fiber and stir rapidly to obtain a mixture. Then, quickly pour the mixture into the cement mixture in step 4) and stir slowly. The polyurethane prepolymer on the surface of the modified PVA fiber foams along the surface direction of the PVA fiber to achieve oriented foaming, thus obtaining a cement-based composite material. The mass ratio of the catalyst, polyol and modified PVA fiber is 1:10~20:10~30. The polyurethane foam structure on the surface of the modified PVA fiber after oriented foaming enhances the density of the concrete.

10. The preparation method according to claim 9, characterized in that, The total amount of the first and second portions of water is in a mass ratio of 1:0.1~1 to the cement. In the concrete preparation method, slow mixing refers to a mixing speed of 50~60 r / min, and fast mixing refers to a mixing speed of 140~150 r / min. In the concrete preparation method, the rapid mixing time in steps 2) and 3) is no more than 60 seconds; In the concrete preparation method, in step 4), the slow stirring time is no more than 10 minutes; In step 5), the catalyst is a mixed catalyst of a tertiary amine compound and an organotin compound; the tertiary amine compound is selected from triethylenediamine or triethylamine; the organotin compound is selected from dibutyltin dilaurate; the mass ratio of the tertiary amine compound to the organotin compound is 1:0.5~0.8; In step 5), the polyol is selected from pentaerythritol and / or glycerol.

11. The application of the concrete as described in claim 7 or 8 in the construction field.

Citation Information

Patent Citations

  • High-strength concrete added with PVA fibers and graphene and preparation method of high-strength concrete

    CN111777387A

  • Concrete modified by graphene / fiber composite material and preparation method thereof

    CN109231914A

  • Self-leveling mortar based on graphene oxide-based layered material modification and preparation method thereof

    CN113372083A

  • High-density anti-radiation anti-crack concrete and preparation method thereof

    CN115196913A